"The general" - Bruckman, Clyde, 1894-1955; Keaton, Buster, 1895-1966; Mack, Marion, 1902-1989; Pittenger, William, 1840-1904.; Joseph M. Schenck Productions; Cinetel Films ([Los Angeles, CA] : Joseph M. Schenck Productions, 1927)
Johnnie loves his train ("The General") and Annabelle Lee. When the Civil War begins he is turned down for service because he's more valuable as an engineer. Annabelle thinks it's because he's a coward. Union spies capture The General with Annabelle on board. Johnnie must rescue both his loves. --
Originally distributed by United Artists.
Buster Keaton, Marion Mack, Glen Cavender, Jim Farley, Charles Smith, Frank Barnes, Joe Keaton, Mike Donlin, Tom Nawn.
Cinematographers, Dev Jennings and Bert Haines.
Silent, with English intertitles and musical accompaniment; optional Spanish subtitles.
Winner of the National Film Registry Award
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015).
Keywords: General (Locomotive); Locomotive engineers -- Drama; Railroad trains -- Drama; United States -- History -- Civil War, 1861-1865 -- Drama; Confederate States of America -- History -- Drama; Silent films; Slapstick comedy films; Feature films; Comedy films; Fiction films; Internet videos; Streaming video